1993
DOI: 10.1093/jnci/85.24.2008
|View full text |Cite
|
Sign up to set email alerts
|

Detection of c-Ki-ras Mutation by PCR/RFLP Analysis and Diagnosis of Pancreatic Adenocarcinomas

Abstract: Screening of pancreatic tissue samples obtained by fine-needle aspiration for c-Ki-ras mutation using PCR/RFLP analysis combined with pathologic examination could facilitate diagnosis of pancreatic tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(38 citation statements)
references
References 0 publications
2
35
0
1
Order By: Relevance
“…The method used to detect mutation in the 12th codon of the K-ras gene was a combination of PCR DNA amplification and RFLP analysis (Jiang et al, 1989;Urban et al, 1993). This method is highly specific, as loss of the restriction site at the target is diagnostic for the presence of a mutation (Jiang et al, 1991;Urban et al, 1996;Behn et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The method used to detect mutation in the 12th codon of the K-ras gene was a combination of PCR DNA amplification and RFLP analysis (Jiang et al, 1989;Urban et al, 1993). This method is highly specific, as loss of the restriction site at the target is diagnostic for the presence of a mutation (Jiang et al, 1991;Urban et al, 1996;Behn et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity of the assay was therefore tested by a series of titration experiments. The threshold of detection was one cell with a homozygous mutation in the midst of 102 cells with a wild-type Ki-ras gene (Figure 2) (Urban et al, 1993). Tables I and II. When using the one step PCR-RFLP method no mutation involving the codon 12 of Ki-ras gene was detected in the 20 squamous cell and four adenosquamous cell carcinomas.…”
Section: Methodsmentioning
confidence: 99%
“…In pancreatic cancer, point mutations of the k-ras oncogene have been shown with a prevalence of up to 90% (Almoguera et al, 1988;Hruban et al, 1993;Urban et al, 1993). Several studies have demonstrated the possibility to detect these mutations in pancreatic juice specimens or duodenal fluid (Tada et al, 1993;Trümper et al, 1994;Berthelemy et al, 1995;Van Laethem et al, 1995).…”
mentioning
confidence: 99%